Evaluation of Antibacterial Activity of Essential Oils of Melaleuca cajuputi Powell - Noor Zarina Abd Wahab; Nur Saidatul Aqilah Ja’afar; Samhani Binti Ismail (Journal of Pure and Applied Microbiology, 2022)
Melaleuca cajuputi Powell is a tree species belonging to the family Myrtaceae and is widely used in traditional medicine. This study was conducted to investigate the antibacterial activities of essential oils of M. cajuputi Powell. Antibacterial activity was tested against Gram positive and Gram negative bacteria using the agar disc diffusion method. The essential oils of M. cajuputi were found to exert antibacterial activity against all of the tested bacteria, including Staphylococcus aureus, Streptococcus pyogenes, methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae, and Escherichia coli. The zones of inhibition for S. aureus, S. pyogenes, MRSA, E. coli, and K. pneumoniae were 12.7 mm, 10.7 mm, 10.0 mm, 8.7 mm and 9.3 mm respectively, against 0.714% (w/w) of the essential oils. These results highlighted that Gram negative bacteria are less susceptible to the essential oils of M. cajuputi. A large zone of inhibition might be a sign of a leaching antimicrobial agent. These findings suggest that M. cajuputi is a potential natural antibacterial agent.